2014
DOI: 10.2208/journalofjsce.2.1_299
|View full text |Cite
|
Sign up to set email alerts
|

Water Environments in the Southern Delta of Myanmar During the Rainy Season

Abstract: Some diseases in Myanmar during the rainy season are related to the water environment and the water quality. In order to contribute to ensuring safe water supply, we collected and analyzed water samples in Myanmar in September 2011. Early research had already reported that coliform and E. Coli were detected in all the survey areas. We examined the water quality, especially chemical components harmful for health, and classified the sample waters into water quality-types in order to identify the sources and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to researchers from the city's Health Research Department, acute diarrhea in children under the age of 5 years due to drinking-water contamination is prevalent in Yangon, occurring in 4.74% of 211 households examined (Sulatt et al 2015). Previous studies (Sakai et al 2013;Senda et al 2014;Sulatt et al 2015) have revealed the presence of fecal coliforms in tap water, bottled water, groundwater, and water from reservoirs in the Yangon region. A study team from Japan recommended the dilution of contaminated water with a low-contamination water source as a potential approach to the treatment of drinking-water supplies (Senda et al 2014).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to researchers from the city's Health Research Department, acute diarrhea in children under the age of 5 years due to drinking-water contamination is prevalent in Yangon, occurring in 4.74% of 211 households examined (Sulatt et al 2015). Previous studies (Sakai et al 2013;Senda et al 2014;Sulatt et al 2015) have revealed the presence of fecal coliforms in tap water, bottled water, groundwater, and water from reservoirs in the Yangon region. A study team from Japan recommended the dilution of contaminated water with a low-contamination water source as a potential approach to the treatment of drinking-water supplies (Senda et al 2014).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Previous studies (Sakai et al 2013;Senda et al 2014;Sulatt et al 2015) have revealed the presence of fecal coliforms in tap water, bottled water, groundwater, and water from reservoirs in the Yangon region. A study team from Japan recommended the dilution of contaminated water with a low-contamination water source as a potential approach to the treatment of drinking-water supplies (Senda et al 2014). Tube well water (groundwater) has been used to augment the insufficient water supply from reservoirs in some areas of the city.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation